Clinical-Pathological Features and Outcome of Atypical Anti-glomerular Basement Membrane Disease in a Large Single Cohort - Shen, Cong-rong; Jia, Xiao-yu; Cui, Zhao; Yu, Xiao-juan; Zhao, Ming-hui (Frontiers in Immunology, 2020)
Background Atypical cases of anti-glomerular basement membrane (GBM) disease had absent circulating antibodies but linear IgG deposits along GBM in the kidneys. Herein, we reported the clinical-pathological features and outcome of these rare cases. Methods Linear IgG deposit along GBM were examined by immunofluorescence on renal specimens, with exclusion of diabetic kidney disease. Circulating anti-GBM antibodies were tested by commercial ELISA assay. Clinical, pathological and follow-up data were retrospectively analyzed. Results From 2013 to 2018, a total of 60 patients were diagnosed as atypical anti-GBM disease. They had a male predominance, with an average age of 51.7±15.6 years. 3(5.0%) patients had alveolar hemorrhage. 45.0% of them presented with acute kidney disease. All patients had linear IgG deposit along GBM, some in addition on tubular basement membrane and/or Bowmans’ capsules. C3 deposition was found in 65.0% of the patients. 41.7%(25/60) of the patients showed crescent formation and the percentage of crescent was (34.7±23.5)% in those patients. They had higher prevalence of hematuria and C3 deposit, higher levels of serum creatinine, worse renal and patient survival than those without crescent (P<0.05). During the follow-up of 35.7±21.4 months, 14 (23.3%) patients progressed to ESRD. The serum creatinine on diagnosis [per 200μmol/L increase, HR(95%CI ): 2.663(1.372,5.172), P=0.004], serum C3(per 0.1g/L increase, HR(95%CI ): 0.689(0.483,0.984), P=0.040) and the intensity of kidney C3 staining (per 1+ increase, HR(95%CI ): 2.770(1.115,6.877), P=0.028) were independent predictive factors for kidney outcome. 9(15.0%) patients died of all causes. Conclusions Atypical anti-GBM disease manifested milder kidney injury and scarce pulmonary hemorrhage compared to the classical cases. Though heterogeneous, a substantial number of the patients had complement activation and crescent formation. Patients having crescents presented with more severe clinical course and worse outcomes. The poor kidney and patient prognosis emphasize prompt interventions from physicians. The immunosuppressive intervention was not associated with kidney or patient outcome. Further studies are needed to address the optimal therapeutic regimen.